Infrastructures of apocalypse : American literature and the nuclear complex - Hurley, Jessica (Professor of literature) (Minneapolis, MN : University of Minnesota Press, 2020)
"A new approach to the vast nuclear infrastructure and the apocalypses it produces, focusing on Black, queer, Indigenous, and Asian American literatures"--
Introduction: End Times -- White Sovereignty and the Nuclear State -- Civil Defense and Black Apocalypse -- Star Wars, AIDS, and Queer Endings -- Nuclear Waste, Native America, Narrative Form -- Coda: Nuclear Entanglements.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 28, 2020).
JSTOR
Keywords: Nuclear warfare in literature; American literature -- 20th century -- History and criticism; American literature -- Minority authors -- History and criticism; Apocalyptic literature -- History and criticism; End of the world in literature; Minorities in literature; Nuclear warfare and literature; Apocalypse in literature; Guerre nucléaire dans la littérature.; Littérature américaine -- 20e siècle -- Histoire et critique; Littérature américaine -- Auteurs issus des minorités -- Histoire et critique; Littérature apocalyptique -- Histoire et critique; Fin du monde dans la littérature.; Guerre nucléaire et littérature.; LITERARY CRITICISM / American / General; Apocalypse in literature; American literature; American literature -- Minority authors; Apocalyptic literature; End of the world in literature; Minorities in literature; Nuclear warfare and literature; Nuclear warfare in literature; 1900-1999; Criticism, interpretation, etc